Perspektif Nilai Tellu Cappa Terhadap Perilaku Abusive Language Siswa SMK di Soppeng - Ummu Saada; Suciani Latif; Aswar; Muhammad Ilham Bakhtiar (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the description of abusive language behavior among students at SMK Negeri 3 Soppeng, focusing on three main research questions: (1) the general overview of abusive language behavior tendencies, (2) the specific forms of dominant behavior, and (3) the influence of digital media use on such behavior. This phenomenon is crucial as verbal aggression becomes increasingly normalized in adolescent social interactions. This study employed a descriptive quantitative approach involving 36 tenth-grade students identified as having high levels of verbal aggression. Data were collected using an Abusive Language Scale adapted from the Verbal Aggressiveness Scale (VAS) and analyzed using descriptive statistical techniques. The results showed that: (1) the majority of students (69%) were in the high category of abusive language use; (2) the most dominant forms of behavior included the use of profanity (27%), insulting expressions (22%), and aggressive language during emotional states (20%); and (3) 19% of abusive language use occurred in digital media, influenced by the imitation of social media content. These findings emphasize the need for group counseling interventions based on the Bugis cultural values of Tellu Cappa (Cappa Lila). It is concluded that the internalization of the